2022
DOI: 10.1186/s13012-022-01223-6
|View full text |Cite
|
Sign up to set email alerts
|

Trends in guideline implementation: an updated scoping review

Abstract: Background Guidelines aim to support evidence-informed practice but are inconsistently used without implementation strategies. Our prior scoping review revealed that guideline implementation interventions were not selected and tailored based on processes known to enhance guideline uptake and impact. The purpose of this study was to update the prior scoping review. Methods We searched MEDLINE, EMBASE, AMED, CINAHL, Scopus, and the Cochrane Database … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 168 publications
0
43
0
Order By: Relevance
“…This illustrates that it is important to include all stakeholders in such a change process. A recent literature review also showed that stakeholder engagement is increasingly used in guideline implementation 50. After implementation of the protocol we never observed a drop in LBP patients coming to the ED.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…This illustrates that it is important to include all stakeholders in such a change process. A recent literature review also showed that stakeholder engagement is increasingly used in guideline implementation 50. After implementation of the protocol we never observed a drop in LBP patients coming to the ED.…”
Section: Discussionmentioning
confidence: 50%
“…A recent literature review also showed that stakeholder engagement is increasingly used in guideline implementation. 50 After implementation of the protocol we never observed a drop in LBP patients coming to the ED. A more difficult barrier to tackle was the high turnover of trainees rotating at the ED and involved in managing the target patient population.…”
Section: Discussionmentioning
confidence: 85%
“…Moreover, Implementation tools will include customized computerized provider order entry (CPOE) with order sets integrated into electronic health record systems at selected pilot sites throughout Saudi Arabia. Local guideline implementation strategies/interventions may also include: leadership commitment and engagement, dissemination and communication, regular training and education, regular audit and feedback to identify facilitators and barriers, and patients as change champions [71][72][73][74].…”
Section: Guideline Dissemination and Implementationmentioning
confidence: 99%
“…Clinical practice guidelines are systematically developed statements to assist healthcare professionals in evidence-informed decision making 1. They include recommendations based on the best available evidence and aim to reduce practice variations in planning and delivering healthcare interventions 2. Clinicians are therefore encouraged to use guidelines to improve patient health outcomes, the quality of clinical decisions, and the safety and cost-effectiveness of care 3.…”
Section: Introductionmentioning
confidence: 99%